2021
DOI: 10.1007/s00259-021-05196-4
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 expression in glioblastoma tissue and the potential for PET imaging and treatment with [68Ga]Ga-Pentixafor /[177Lu]Lu-Pentixather

Abstract: Purpose CXCR4 (over)expression is found in multiple human cancer types, while expression is low or absent in healthy tissue. In glioblastoma it is associated with a poor prognosis and more extensive infiltrative phenotype. CXCR4 can be targeted by the diagnostic PET agent [68Ga]Ga-Pentixafor and its therapeutic counterpart [177Lu]Lu-Pentixather. We aimed to investigate the expression of CXCR4 in glioblastoma tissue to further examine the potential of these PET agents. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
(40 reference statements)
0
27
0
Order By: Relevance
“…Several studies have demonstrated that CXCR4 expression in glioblastoma is associated with a poorer prognosis and more infiltrative phenotypes. For an example, Jacobs et al showed that CXCR4 mRNA expression correlates with WHO glioma grade, with a relatively higher expression of CXCR4 in high grade gliomas (obtained from 284 samples), whereas normal brain tissue was CXCR4 mRNA negative [ 23 ]. In their study, variable CXCR4 expression was demonstrated in 38% of the cores in glioblastoma cells, and CXCR4 expression was high in only a subset of glioblastomas.…”
Section: Cxcr4 In Solid Malignanciesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated that CXCR4 expression in glioblastoma is associated with a poorer prognosis and more infiltrative phenotypes. For an example, Jacobs et al showed that CXCR4 mRNA expression correlates with WHO glioma grade, with a relatively higher expression of CXCR4 in high grade gliomas (obtained from 284 samples), whereas normal brain tissue was CXCR4 mRNA negative [ 23 ]. In their study, variable CXCR4 expression was demonstrated in 38% of the cores in glioblastoma cells, and CXCR4 expression was high in only a subset of glioblastomas.…”
Section: Cxcr4 In Solid Malignanciesmentioning
confidence: 99%
“…Jacobs et al went on to correlate in vitro CXCR4 expression with in vivo 68 Ga-Pentixafor uptake on PET/CT imaging in seven patients [ 23 ]. Five (71%) of the seven patients showed low to moderate tracer uptake, which did not fully correspond with CXCR4 IHC where all patients showed large intra-tumour variation for CXCR4 staining, even within one section.…”
Section: Cxcr4 In Solid Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to the sometimes-pronounced CXCR4 expression observed in ex vivo immunohistochemistry studies using tumor biopsies, the corresponding in vivo [ 68 Ga]Pentixafor PET/CT studies demonstrated a very heterogeneous, often modest, and in some cases even absent CXCR4-mediated tracer uptake in solid cancers [ 26 , 27 , 28 , 29 ], limiting the broad diagnostic application of this imaging approach. To date, only few solid tumor entities have shown pronounced overexpression of CXCR4, as assessed by PET/CT.…”
Section: Cxcr4-targeted Theranostics In Cancer and Its Limitationsmentioning
confidence: 99%